PENGARUH FOOT HYDROTHERAPY DENGAN AIR GARAM TERHADAP KUALITAS TIDUR PENDERITA HIPERTENSI DI PUSKESMAS DENPASAR TIMUR - andriani, ni putu clarissa; Sutriska Sagala, Martha (Jurnal Kesehatan Marendeng, 2025)
Hypertension is the leading cause of death worldwide, characterized by blood pressure exceeding 140/90 mmHg. Hypertension causes headaches, leading to discomfort at night and poor sleep quality. Sleep quality is a person's satisfaction with their sleep. The aim of this study was to analyze the effect of foot hydrotherapy with salt water on improving sleep quality in hypertensive patients at the East Denpasar II Community Health Center. The research method used was a pre-experimental design with a one-group pre-post test design. The study subjects were hypertensive patients with poor sleep quality in the service area of Puskesmas II Denpasar Timur from July 1–7, 2024, with a sample size of 24 participants using non-probability sampling (saturation sampling). The tool used was the Pittsburgh Sleep Quality Index (PSQI) questionnaire. The Wilcoxon test was used to analyze the data in this study. The results showed a p-value of 0.000. The null hypothesis (Ho) was rejected because p < 0.05. There was a significant effect of foot hydrotherapy with saltwater on improving sleep quality in hypertensive patients at Puskesmas II Denpasar Timur. The results of this study are expected to assist healthcare workers in providing counseling to hypertensive patients, particularly regarding the application of foot hydrotherapy with saltwater as a non-pharmacological technique and an alternative to address poor sleep quality issues.